Production of lactobionic acid using an immobilized cellobiose dehydrogenase/laccase system on magnetic chitosan spheres. (January 2021) - Yang, Junhua; Xu, Peng; Long, Liangkun; Ding, Shaojun
Graphical abstract: Production of lactobionic acid using an immobilized cellobiose dehydrogenase/laccase system on magnetic chitosan spheres Highlights: A new cellobiose dehydrogenase was identified from Aspergillus fumigatus . Immobilized Af CDH showed better thermal stability than free enzyme. Immobilized Af CDH/ Laccase system was efficient for oxidizing lactose into lactobionic acid. Immobilized bi-enzyme system has good reusability retaining 70 % activity after 10 cycles. Abstract: Lactobionic acid (LBA) has numerous promising applications in food, pharmaceutical, cosmetics and chemical fields. LBA can be produced by cellobiose dehydrogenase (CDH)/laccase (Lac) bi‐enzymatic system with redox mediator, in which CDH catalyzes the oxidation of lactose into LBA, while LAC serves as a regenerative enzyme to simultaneously regenerate the redox mediator as electron acceptor for CDH. Despite this CDH/LAC system is effective in catalyzing the oxidation of lactose into LBA, easy deactivation of free enzymes throughout the biocatalysis process limited its industrial implementation. In this study, a new cellobiose dehydrogenase from Aspergillus fumigatus ( Af CDH) was characterized. Af CDH and LAC were separately immobilized on the glutaraldehyde-modified magnetic chitosan spheres (MCS) with the activity yields of immobilization 61.54 % and 14.1 %, respectively. Immobilized Af CDH displayed better thermal stability and retained 60 % of initial activity after incubation at 50 °C for 4 h, in contrast, the residual activity of free Af CDH was hardly detected under the same condition. Our study demonstrated that the immobilized Af CDH/LAC system was efficient for bioproduction of LBA. 100 g/L of lactose was completely converted to LBA with a space-time yield of 7.14 g/L h This immobilized Af CDH/LAC system had good reusability and retained 70 % activity after 10 cycles of reuse.